Synchronization in cooperative communication - Hong, Chao. (2010)
In recent years, cooperative communication has emerged as a hot topic in wireless communication. Through cooperation, diversity of the communication system is improved, which increases throughput or reliability of the network. Since different users are distributed in different locations and usually there is no central controller, synchronization of them becomes extremely difficult. Hence, for cooperative communication to be practical, it is crucial to develop effective distributed time synchronization and carrier frequency synchronization schemes. This objective of this project is to design the time synchronization algorithms for cooperative communication. We have made the following contributions to this project: We have studied the time synchronization problem in a simple cooperative communication system and done the simulation in the Matlab. In this system, we have estimated the time delay in the received signal. We did this by sending a training signal to the receiver. Using this method, we have estimated the time delays for different users. We also have done the channel estimation by sending pilots signal. Using the estimated channels, we have done the equalizations for the received signal. For the time delay estimation, there always will be errors. We have analyzed the effects of estimated time errors on the equalization performance of the system.